Sepsis calculator to support antibiotic stewardship in early-onset neonatal sepsis: a meta-analysis - Rinawati Rohsiswatmo; Hardya Gustada Hikmahrachim; Dinarda Ulf Nadobudskaya; Sonia Miyajima Anjani; Albert You (Paediatrica Indonesiana, 2018)
Background Establishing a diagnosis of neonatal sepsis is difficult. As such, appropriate timing of antibiotic therapy remains the biggest challenge. As a consequence of non-definitive diagnoses, inappropriate antibiotic administration is common. Recently, a sepsis calculator to estimate risk of early-onset sepsis (EOS) based on both maternal risk factors and infants' clinical presentation was established. Objective To determine the impact of the sepsis calculator in daily clinical settings, especially with regards to antibiotic usage. Methods A literature search of Pubmed, EBSCO, Embase, and Scopus database from January 2011 (after sepsis calculator was established) to June 2018 was performed. We included observational studies that compared the sepsis calculator to recent neonatal sepsis guidelines in terms of antibiotic administration, blood culture, and admission to the neonatal intensive care unit (NICU). The literature search, validation study, and assessment risk of bias were done independently by our four authors, while the first author did the statistical analysis. Results Of the 35 studies identified, 5 cohort studies met the criteria, with a total sample size of 18,352 infants from various countries. We developed a fixed-effect meta analysis of the data. The use of the sepsis calculator significantly reduced inappropriate use of antibiotics [RR 0.46; 95%CI 0.41 to 0.51; z=13.57; P<0.001], blood culture sampling [RR 0.46; 95%CI 0.40 to 0.52; z=12.11; P<0.001), and higher neonatal care level admissions [RR 0.68; 95%CI 0.59 to 0.78); z=5.47; P<0.001). No safety issues were reported from studies using the sepsis calculator. Conclusion The new EOS risk estimation using a neonatal sepsis calculator is an easy, effective, and safe tool to improve appropriate antibiotic use and outcomes. This calculator is ready to be implemented in all levels of neonatal care units.